Herbal extracts in diets for broilers. - PETROLLI, T. G. (2012)
The objective of this study was to evaluate the effect of feeding herbal extracts for broilers on performance and histology of the intestinal mucosa and its effects on the profiting from the metabolizable energy of experimental diets. For so, two experiments were conducted. In experiment I, the inclusion of different herbal extracts in diets on performance and intestinal histology of broilers was evaluated, and in experiment II, the values of apparent metabolizable energy and metabolizable energy corrected by the nitrogen balance of the experimental diets were studied. Treatments consisted of: positive control diet; positive control + avilamycin; negative control; negative control + 100 ppm of a complex containing three different herbal medicines (pepper, cinnamon and oregano); negative control + 75 ppm garlic extract; negative control + 150 ppm garlic extract. In the performance experiment, which comprised the period of 1 to 40 days of age, 960 male broilers were distributed in a randomized block design, with six treatments and eight replicates, with 20 birds per experimental unit. In experiment II, the method adopted was the traditional of total excreta collection with male broiler chicks in the age of 14 to 24 days, in a completely randomized design, with six treatments and eight replicates with five birds per experimental unit. The intestinal villus height was improved with addition of the composite containing the three herbal extracts; however, crypt depth and villus/crypt ratio were not affected. The use of herbal extract in diets for broilers promotes performance similar to that with the use of antibiotics. Herbal extracts can be incorporated into diets replacing antibiotics without compromising the metabolizable energy of diets, performance or intestinal mucosa for broilers in the period of 1 to 40 days of age.